Prevalence of low back pain and its associated factors among weavers in low- and middle- income countries: a systematic review and meta-analysis - Abebe Kassa Geto; Leykun Berhanu; Gete Berihun; Chala Daba; Belay Desye (BMC Musculoskeletal Disorders)
Abstract Introduction Low back pain, one of the musculoskeletal disorders is among the major global public health problems and contributors to disability and workers’ absence in occupational areas which certainly disrupts work productivity and the expected results. Though various studies investigated low back pain, the results were inconsistent and inconclusive enough, and there is no representative data in low- and middle-income countries on this public health concern. This in turn hinders the efforts of various intervention activities. Therefore, this systematic review and meta-analysis was conducted to determine the pooled prevalence of low back pain and its associated factors among weavers of low- and middle-income countries. Methods All the relevant articles were retrieved from databases such as PubMed/MEDLINE, CINAHL, LIVIVO, African Journals Online, African Index Medicus (AIM), HINARI, Science Direct, Web of Science, Cochrane Library, Google Scholar, Semantic Scholar, and Google. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline was followed for this study. The extracted data were analyzed using STATA 17 software. With a 95% confidence interval, this meta-analysis with the random-effects model was conducted to determine the pooled prevalence.  Result A total of twenty articles with 7211 study participants were included in this meta-analysis. The pooled prevalence of low back pain was 55.81%. Age, working in a chair with no back support, working in an uncomfortable posture, work experience, and job stress were the factors significantly associated with low back pain. Conclusion A high prevalence of low back pain among weavers in low-and middle-income countries was registered. This indicates the need to take effective intervention measures. Rigorous provision of ergonomic training, providing lengthy breaks, improving workplace ergonomic design, and increasing job satisfaction are recommended.